Lateral behaviour of PT segmental bridge columns with Ultra High Strength Concrete (UHSC) - Nikbakht, E. (International Association for Bridge and Structural Engineering (IABSE), 2018)
In recent years, application of precast post-tensioned (PT) segmental columns consisting of a number of precast segments and footing foundation aligned and connected altogether by post tensioning strands, has shown increasing focus in seismic regions due to their advantages over traditional columns including self-centering capability with low residual displacement and permanent deformation under severe lateral seismic loading. Recently, there have been an emerge of interest to use ultra-high strength concrete (UHSC) due to their great tensile and compressive strengths. In this study, a three dimensional (3D) nonlinear finite element model for PT segmental columns are developed and the results are validated with the experimental test conducted. A parametric study is carried out to investigate the influence of UHCS with different compressive strengths of 126 MPa, 150 MPa and 193 MPa; and tensile strengths of 6.0, 8.9 and 12.3 MPa on lateral response of PT segmental columns. In this study, PT segmental columns with normal strength; High strength concrete fully replaced with normal strength concrete throughout the columns; and UHSC as jacketing around the first segment are investigated. The influence of compressive strength and tensile strength on stiffness, lateral load capacity and ductility of the segmental columns with different concrete strengths are discussed. Also, strengthening of PT segmental columns with UHSC jacketing were examined and the results are compared. Â© IABSE Conference, Kuala Lumpur 2018: Engineering the Developing World - Report. All rights reserved.